2012
DOI: 10.5194/hess-16-1501-2012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spatial and temporal fine sediment dynamics in a small river

Abstract: Abstract. Empirical measurements on fine sediment dynamics and fine sediment infiltration and accumulation have been conducted worldwide, but it is difficult to compare the results because the applied methods differ widely. We compared common methods to capture temporal and spatial dynamics of suspended sediment (SS), fine sediment infiltration and accumulation and tested them for their suitability in a small, canalized river of the Swiss Plateau. Measurement suitability was assessed by data comparison, relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
23
1
2
Order By: Relevance
“…This suggests that although reference and TIMS loads may be highly correlated, within‐site variations act to bias the replicate estimates within the cross section. This variability was also observed by Schindler Wildhaber et al ., (), highlighting the sensitivity of flux estimates to sampler positioning. The criteria for determining the sampler location should therefore, wherever possible, be consistent between sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that although reference and TIMS loads may be highly correlated, within‐site variations act to bias the replicate estimates within the cross section. This variability was also observed by Schindler Wildhaber et al ., (), highlighting the sensitivity of flux estimates to sampler positioning. The criteria for determining the sampler location should therefore, wherever possible, be consistent between sites.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, Schindler Wildhaber et al . () suggested that both TIMS and turbidity sensors are suitable for capturing large‐scale spatial and temporal variations in SSCs or suspended sediment (SS) loads. They found the total weekly SS load from TIMS was significantly correlated with mean weakly SSCs, with spearman rank correlations of 0.8 ( n = 212), 0.2 ( n = 204) and 0.7 ( n = 204).…”
Section: Introductionmentioning
confidence: 97%
“…This is likely a consequence of bed-form heterogeneity, and variations in the source and type of sediment. Sampler location should therefore, wherever possible, be consistent between sites (Schindler Wildhaber et al, 2012).…”
mentioning
confidence: 99%
“…However, the laboratory tests were done with chemically dispersed sediment, which prevents the agglomeration and settling processes that occur in natural systems, thus representing a worst‐case scenario for sediment loss. Previous studies have shown that the Phillips sampler can collect a statistically representative sample for analysis of particle size distribution in natural systems, even when flows are elevated (Perks et al, ; Perks et al, ; Schindler Wildhaber, Michel, Burkhardt‐Holm, Bänninger, & Alewell, ; Smith & Owens, ; D. Walling, ). Therefore, it is likely that the average particle size distribution of the sample collected by the PASS and Phillips samplers are representative of the particle size distribution of suspended sediment in Loders Creek during the two sampled events.…”
Section: Resultsmentioning
confidence: 99%